SERTIFIKASI DAN PERMASALAHANNYA - Deswika Khairotul Nisa; Sofia Oktoviani; NurDahlia; Rizki Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Educators hold a strategic role in the national education system as they are directly involved in the learning process and character development of students. Therefore, improving teacher competence is a top priority for the government in efforts to enhance education quality. The teacher certification program is designed to ensure that every educator meets the established standards of professional, pedagogical, social, and personal competencies. This study aims to examine the implementation of teacher certification policies and the obstacles encountered during the process. The method used is a literature review by analyzing various relevant sources. The findings indicate that certification policies have had a positive impact on teacher professionalism, work motivation, and mastery of technology and effective teaching methods. However, implementation still faces challenges such as complicated bureaucracy, unequal training access between teachers in urban areas and those in 3T regions, and the lack of ongoing evaluation after certification. Additionally, some teachers pursue certification merely to fulfill administrative requirements without fully understanding the essential goal of improving education quality. To address these issues, it is necessary to digitize administrative processes, conduct continuous training, carry out regular evaluations, and provide intensive assistance, especially for teachers in remote areas. With the right strategies and sustainable policy support, teacher certification is expected to become an effective instrument in improving the overall quality of education in Indonesia.